Self-Nitrogen-Doped Carbon from Plant Waste as an Oxygen Electrode Material with Exceptional Capacity and Cycling Stability for Lithium–Oxygen Batteries - Wang, Meiling; Yao, Ying; Tang, Zhenwu; Zhao, Tuo; Wu, Feng; Yang, Yufei; Huang, Qifei (ACS applied materials & interfaces, 2018)
To promote the development of electric automobiles, high energy density and high-power batteries are urgently needed. More and more attention has been paid to look for high-performance cathode catalysts for Li–O2 batteries. However, the sluggish kinetic reaction, the stacking of electrical insulation product of Li2O2, and the undesired parasitic reaction restrict their capacity and present poor cycling performance. Here, we prepared nitrogen self-doped activated carbons (N-PIACs) derived from the plant waste (poplar inflorescence) through the activation and slow pyrolysis carbonization method, exhibiting several advantages. The materials presented a three-dimensional interconnecting pore structure and a high surface area. Besides, defects and functional groups doped by nitrogen as active sites improved electrochemical catalysis activity. The Li∥N-PIACs–O2 battery delivered a high specific capacity of 12060 mAh/g, which was 2.3 times that of the pristine plant waste-based Li–O2 battery (N-PICs). In addition, it presented more excellent cycling stability than other common carbon materials. In this study, we developed a functional carbon nanomaterial from cheap natural materials, which might become a highly attractive subject, indicating that this strategy could strengthen the properties of Li–O2 batteries.